Modern issues of pedagogy and psychology: theoretical and methodological approaches and practical research results - Gadzaova L. P., Makambaeva Y. Z., Murzaeva B. T., Satyvaldiev A. S., Shemiakina S. A., Sakharchuk E. I., Anikin V. M., Kupovykh G. V., Ryspaeva C. K., Akhunzhanova M. K., Maslennikova S. F., Medvedeva A. A., Temirkanova T. E., Doroschuk E. S., Zaritskaia V. V., Kozlova M. A., Kozlov A. V., Sabodina E. P., Kugai A. I., Kugai A. I., Bashkireva T. V., Bashkireva A. V., Shatokhina L. V., Smykovskaia T. K., Sergeev N. K., Korotkov A. M., Korepanova M. V., Rodionova I. V., Shapirova R. R., Akhtarieva R. F., Khotuliova O. V., Egorova G. V., Barashkina S. B., Zaluzhnaia M. V., Kostenko E. G., Kugai A. I., Isakova T. I., Zanin D. S. (Modern issues of pedagogy and psychology: theoretical and methodological approaches and practical research results, 2025)
the chapter presents a theoretical and methodological analysis of the phenomenon of work-life balance. The main methodological approaches to the study of balance in life are structured and characterized. The authors have identified indicators of work-life balance.
Keywords: субъективное благополучие; удовлетворенность жизнью; subjective well-being; life satisfaction; work-life balance; баланс работы и жизни; сферы жизни; феномен баланса в жизни; конфликт ролей; дисбаланс работы и личной жизни; spheres of life; the phenomenon of balance in life; conflict of roles; imbalance of work and personal life